Low-income Families Guide Innovation: Application of Human-Centered Design - Daan de Jong; Alicia Atkinson (Journal of Participatory Research Methods)
The Prosperity Agenda (TPA) is a nonprofit organization whose human-centered design process centers on the belief that all people are resilient and resourceful. From 2016 to 2019, with support from the W.K. Kellogg Foundation, they collaborated with the Washington State Department of Commerce to design and implement a new program to encourage two-generational savings among families receiving social welfare assistance. Innovative classroom events focused on savings were a direct outgrowth of TPA’s work with families experiencing poverty. The positive results of the yearlong pilot confirmed the idea that an intervention rooted in human-centered design and guided by both the experiential wisdom of low-income families and the deep expertise of event facilitators would help families build financial resilience.